Victimology Review of the Legal Protection of Victims of the Crime of Human Trafficking - Bintara Sura Priambada; Dania Rama Pratiwi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The emergence of various problems in society and the victims or the victims of crime in particular (adults, children) is a problem for crime victims. Human trafficking is a modern trade that not only robs the victim of human rights but also makes a person vulnerable to acts of persecution or physical torture and forced labor. Women who are objectified as commercial sex workers, or in the labor sector who often receive inhumane treatment. Meanwhile, victims who are trafficked to be used as illegal labor with low wages and even many who become beggars occur in children. Preventive legal protection, namely prevention to reduce the risk of potential victims in the form of socializing the behavior of victims in responding to criminal acts of trafficking, people prefer to take non-litigation in order to obtain compensation. This includes the commitment of law enforcement officers who have not been based on the interests of the victims. An assessment of a good law can then sort through several approaches, including through the components that must be included in the legal system. Three components that must be included in the legal system are structural, substantive, and cultural components. The repressive form of legal protection has also referred to the rights of victims; a) asking the victim's identity, b) informing the victim about the concept of service, c) informing the victim that all services are free (non-cost), d) informing the client's rights. This should be criticized that it is an illogical thing which is the pockets of Indonesian workers and indicated the potential for criminal acts of trafficking in persons to occur, it is necessary to understand that the occurrence of criminal acts of trafficking in persons can occur during pre-placement, placement, and post-placement of Indonesian workers.